Detection of N-Te bonds in the as-deposited amorphous nitrogen-doped GeTe-based phase change alloys using N K-edge XANES spectroscopy and their impact on crystallization - Krbal, Miloš; Kolobov, A. V.; Fons, P.; Mitrofanov, K. V.; Tamenori, Y.; Hyot, B.; Andre, B.; Tominaga, J. (Elsevier Science SA, 2017)
Using N K-edge XANES studies, we demonstrate a noticeable difference in local structure around the nitrogen atoms in as-deposited amorphous and annealed N-doped GeTe-based phase change alloys. The pronounced changes appear as a approximate to 2 eV shift in the absorption edge to higher photon energies and the overall shape of the XANES spectrum. Comparison of the experimental XANES spectrum of the as deposited amorphous phase with ab-initio XANES simulations discloses that the as-deposited phase mainly consists of the NGe3 and the NTe3 pyramidal units in approximately equal concentration. When annealed, NTe3 units gradually rebond to the NGe3 units and at the same time N atoms diffuse through the amorphous phase to form the GexNy aggregates. Upon long-standing annealing at 400 degrees C a compact interlayer of Ge3N4 is formed in the crystalline phase.
Detekce N-Te vazeb v dusíkem dopovaných amorfních phase change slitinách na bázi GeTe pomocí XANES spektroskopie N K-hrany a jejich dopad na krystalizaci
Keywords: X-ray absorption spectroscopy; Phase-change memory; Local structure; RTG absorpční spektroskopie; Phase-change paměť; lokální struktura